A Simulation Technology for a Full Cycle of Steel Line Pipe Manufacturing Operations. (30th May 2011) - Aleshin, Vladimir V.; Kobyakov, Viacheslav V.; Seleznev, Vadim E.
Abstract : At present day, pipe mill engineers have to deal with challenging technological problems of heavy-wall and high-strength line pipe manufacturing. Numerical analysis of welded large-diameter pipe manufacturing stages is the most efficient way to solve these problems. Corresponding computational technologies and applied software were developed at Physical & Technical Center. Numerical structural analysis of steel plates at various stages of line pipe manufacturing is performed by the finite element method, accounting for geometric and material nonlinearities. The only thing to be done by the engineer in such analysis is to specify required input parameters. All the further process is software controlled. The discrepancy between the numerical analysis results and measured data in the overwhelming majority cases did not exceed 1%.